Role of Autophagy in Lung Inflammation - Painter, Jacob D.; Galle-Treger, Lauriane; Akbari, Omid (Frontiers in Immunology, 2020)
Autophagy is a cellular recycling system found in almost all types of eukaryotic organisms. The system is made up of a variety of proteins which function to deliver intracellular cargo to lysosomes for formation of autophagosomes in which the contents are degraded. The maintenance of cellular homeostasis is key in the survival and function of a variety of human cell populations. The interconnection between metabolism and autophagy is extensive, therefore it has a role in a variety of different cell functions. The disruption or dysfunction of autophagy in these cell types have been implicated in the development of a variety of inflammatory diseases including asthma. The role of autophagy in non-immune and immune cells both lead to the pathogenesis of lung inflammation. Autophagy in pulmonary non-immune cells leads to tissue remodeling which can develop into chronic asthma cases with long term effects. The role autophagy in the lymphoid and myeloid lineages in the pathology of asthma differ in their functions. Impaired autophagy in lymphoid populations have been shown, in general, to decrease inflammation in both asthma and inflammatory disease models. Many lymphoid cells rely on autophagy for effector function and maintained inflammation. In stark contrast, autophagy deficient antigen presenting cells have been shown to have an activated inflammasome. This is largely characterized by a TH17 response that is accompanied with a much worse prognosis including granulocyte mediated inflammation and steroid resistance. The cell specificity associated with changes in autophagic flux complicates its targeting for amelioration of asthmatic symptoms. Differing asthmatic phenotypes between TH2 and TH17 mediated disease may require different autophagic modulations. Therefore, treatments call for a more cell specific and personalized approach when looking at chronic asthma cases. Viral-induced lung inflammation, such as that caused by SARS-CoV-2, also may involve autophagic modulation leading to inflammation mediated by lung resident cells. In this review, we will be discussing the role of autophagy in non-immune cells, myeloid cells, and lymphoid cells for their implications into lung inflammation and asthma. Finally, we will discuss autophagy’s role viral pathogenesis, immunometabolism, and asthma with insights into autophagic modulators for amelioration of lung inflammation.